Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes. - Vintimilla, Beatriz (2010)
When learning a foreign language, there are some factors that influence its mastering. One of them is the interference of the mother tongue. Although this is a very interesting topic, it was difficult to find information specifically about how Spanish structures influence English learning. Therefore, we proceeded to develop the topic: “Native language interference in learning English as a foreign language” due to the fact that there is not enough information about interference in our country.